Interaction Between Moderate Earthquakes and Volcanic Eruptions: Analyses of Global Data Catalog - Takeshi Nishimura (Geophysical Research Letters)
Abstract The interaction between earthquakes and volcanic eruptions is investigated by analyzing a modern seismic data catalog of centroid moment tensor solutions and eruption records summarized by the Smithsonian Institution. To determine the average features of the interactions, the numbers of earthquakes that occurred before and after the initiation of each eruption with a volcanic explosivity index of larger than or equal to 2 are analyzed. The results show that moderate earthquakes, which have moment magnitudes of 5 to 6 (Mw 5–6), are activated within a horizontal distance of 50 km from volcanoes for about 0.3 years after the initiation of an eruption. About 13% of volcanic eruptions are accompanied by moderate earthquakes. The occurrence possibility of earthquakes every 0.1 years for 0.3 years after an eruption is about 5 times larger than normal. No significant dependence on the tectonic settings and major rock types is recognized.